Reference values of parathyroid hormone in very low birth weight infants - Matejek, Tomas; Zapletalova, Bara; Stranik, Jaroslav; Zaloudkova, Lenka; Palicka, Vladimir (Annals of clinical biochemistry, 2024)
PURPOSE: The primary goal was to estimate reference values of parathyroid hormone (PTH) in very low birth weight infants without severe neonatal morbidity. A secondary objective was to assess the relationship between PTH serum levels and selected laboratory markers of bone metabolism. METHODS: Ninety two infants with birth weight less than 1500 g met the inclusion criteria of the study. Serum levels of PTH, 25-hydroxyvitamin-D [25(OH)D], C3-epi-25(OH)D, total calcium, phosphorus, and alkaline phosphatase, and urinary levels of calcium, phosphorus, and creatinine were examined on day 14 and subsequently every 2 weeks until discharge. RESULTS: Of the total 167 serum samples examined for PTH levels in infants without 25(OH)D deficiency the estimated range was 0.9-11.9 pmol/l (8.5-112.3 pg/mL). During the first month, no statistically significant correlation was observed between PTH level and that of 25(OH)D, C3-epimers of 25(OH)D, S-Ca, S-P, or ALP, nor with urinary excretion of calcium and phosphorus. From the second month of life, there was a moderately significant correlation between PTH and 25(OH)D (Rho = -0.40, P =< .001), between PTH and calcium/creatinine ratio (Rho = -0.56, P = < .001), and between PTH and phosphorus/creatinine ratio (Rho = 0.51, P = < .001). CONCLUSIONS: The physiological range for PTH levels for preterm neonates without 25(OH)D deficiency was estimated as 0.9-11.9 pmol/l (8.5-112.3 pg/mL). It seems that elevation of serum PTH above this range can be considered as hyperparathyroidism in very low birth weight infants.
Keywords: alkalická fosfatasa; reference range; kreatinin; vápník; mužské pohlaví; preterm infants; Infant, Very Low Birth Weight; Parathyroid hormone; Alkaline Phosphatase; Calcium; Infant, Newborn; Vitamin D; referenční hodnoty; ženské pohlaví; novorozenec; Humans; Reference Values; vitamin D; parathormon; Creatinine; Parathyroid Hormone; hyperparathyroidism; fosfor; Female; Phosphorus; novorozenec s velmi nízkou porodní hmotností; lidé; Male